Replacing arginine 99 with leucine to study the kinetics of interconnected allosteric interactions between FFAR4 and naturally occurring fatty acids. (15th July 2022) - Niu, Bo; Lu, Dingqiang; Zheng, Ziqing; Yuan, Shuai; Pang, Guangchang
Graphical abstract: Highlights: First study effect of replacing Arg99 with Leu on hFFAR4 recognition FFAs. Mathematical models were used to compare kinetic parameters of different FFAs. The Ka of most fatty acids increased after replacing arginine 99 with leucine. Arg99 plays an important role in the recognition of fatty acid carboxyl groups. The recognition pattern of CC double bonds in fatty acids was discovered. Abstract: The long-chain fatty acid receptor FFAR4 is the main G-protein-coupled receptor in the body for detecting long-chain fatty acids. It has been shown that Arg99 may be an important residue for fatty acid recognition and for the activation of hFFAR4, though direct evidence is still lacking. In this study, Arg99 on hFFAR4 was substituted with leucine by genetic manipulation, and a double-layer gold nanoparticle biosensor based on hFFAR4 (Arg99 → Leu) was constructed. The interconnected allosteric interaction between 11 naturally occurring fatty acid ligands and the receptor was determined. The results showed that Arg99 is the key residue on hFFAR4 for the recognition of the carboxyl group on fatty acids. This study offered direct quantitative evidence for the role played by different residues in receptor–ligand recognition and interconnected allosterism, providing a new approach for investigating the mechanisms and kinetics of interconnected receptor–ligand allosterism.